Remarkable bone formation following gefitinib for extensive lytic bone metastasis: A report of two cases - Bashir, E.S.; Kwan, A.K.N.; Chan, C.Y.W.; Kwan, M.K. (Hong Kong University Press, 2016)
Gefitinib inhibits the epidermal growth factor receptor tyrosine kinase and improves survival in patients with non-small-cell lung cancer. We report 2 patients with extensive lytic bony metastasis in the spine and pelvis secondary to advanced pulmonary adenocarcinoma who were treated with gefitinib and had remarkable bone formation in the lytic bone lesions in the spine and pelvis. Surgery for stabilisation was avoided.